L1 mediation in L2 writing within groups of lowproficient students at tertiary level - Noor 'Izzati, Ahmad Shafiai (2016)
The use of Malay as the first language (L1) in learning English as a second language (L2) among low-proficient students at tertiary level has been a constant debate over the years. Previous studies, mainly using quantitative strategies, have generally shown positive preference among these learners while working individually. However there is a need to investigate by using qualitative perspective on how L1 may assist in L2 learning especially in groups, as an alternative approach to language learning among these students. This qualitative case study uses Sociocultural Theory (SCT) as its main theoretical framework, whereby interaction is perceived as an input to trigger the mediated process of human mental functioning. This study aims to investigate the factors for low-proficient Malay students’ use of Malay (L1) during group discussion in English (L2) lesson. This study also investigates the process in which L1 mediation helps them to complete an L2 task conducted in groups. The main data is obtained via audio recording, video recorded observations and stimulated recall interviews on six low-proficient students in an L2 class in one higher education institution in Malaysia. Data was analyzed using thematic analysis approach. The findings show that L1 mediation is applied due to limited vocabulary in L2, difficulty in speech production, and to ensure mutual understanding of speech with one another. The mediation is achieved by employing memory recall, peer corrections, and peer assistance in both L1 and L2 in order to understand instructions in L2 task, to generate ideas in group discussion, and to present ideas into written form in L2. This study contributes to alternative teaching method in the classroom, especially towards tertiary level students with low-proficiency in English, whereby they are allowed to use L1 to mediate their L2 learning. This study also implies a different perspective in the L1 and L2 controversial issue, in which the academic policy and educators’ rules need to be revisited especially if L1 can assist L2 learning.